2010
DOI: 10.1111/j.1469-185x.2010.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Orchid pollination by sexual deception: pollinator perspectives

Abstract: The extraordinary taxonomic and morphological diversity of orchids is accompanied by a remarkable range of pollinators and pollination systems. Sexually deceptive orchids are adapted to attract specific male insects that are fooled into attempting to mate with orchid flowers and inadvertently acting as pollinators. This review summarises current knowledge, explores new hypotheses in the literature, and introduces some new approaches to understanding sexual deception from the perspective of the duped pollinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
202
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(218 citation statements)
references
References 183 publications
(341 reference statements)
2
202
1
4
Order By: Relevance
“…Numerous studies have shown that these color patterns are critically important for plant-pollinator interactions (1)(2)(3)(4)(5)(6)(7)(8). Among the most captivating examples are deceptive orchids that display floral pigment patterns remarkably similar to female bees or wasps to lure male counterparts for pseudocopulation, thereby achieving pollination (9)(10)(11).…”
mentioning
confidence: 99%
“…Numerous studies have shown that these color patterns are critically important for plant-pollinator interactions (1)(2)(3)(4)(5)(6)(7)(8). Among the most captivating examples are deceptive orchids that display floral pigment patterns remarkably similar to female bees or wasps to lure male counterparts for pseudocopulation, thereby achieving pollination (9)(10)(11).…”
mentioning
confidence: 99%
“…Sexual deception, currently known in several genera of orchids, and one genus of Asteraceae and Iridaceae, respectively, is a highly specific pollination mechanism (Gaskett, 2011; Johnson & Schiestl, 2016). Sexually deceptive plants mimic mating signals of their pollinators, such as sex pheromones, morphology, and surface pilosity, and entice their pollinators into attempted copulations with their flowers (Peakall & Whitehead, 2014; Peakall et al., 2010; Schiestl & Schlüter, 2009; Schiestl et al., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for pollinator specificity in sexually By contrast to the lack of pollinator sharing in Chiloglottis and Drakaea revealed by field choice testing, published pollinator lists suggest pollinator sharing may occur in some groups of sexually deceptive, Thynnid-pollinated Caladenia species in eastern Australia (Phillips et al 2009, Gaskett 2010. While most sexually deceptive Caladenia species attract unique pollinators, nine species in the Caladenia reticulata complex are pollinated by Phymatothynnus near nitidus 1, three species of Greencomb Spider Orchids are pollinated by Lophocheilus anilitatus and Caladenia tesselata shares P. near nitidus 1 with the C. reticulata group (Phillips et al 2009, Gaskett 2010. These data contrast markedly with results for Chiloglottis and Drakaea, and suggest that factors other than pollinator specificity may govern reproductive isolation in some Caladenia clades.…”
Section: Introductionmentioning
confidence: 99%
“…Pollination by sexual deception of male insects has evolved independently in multiple lineages of the Orchidaceae principally on two continents, Europe and Australia, and involves hundreds of species (Gaskett 2010). Pollen transfer occurs in sexually deceptive orchids when female mimicking labellum structures stimulate mating behaviours in deceived males Francisco 2014, Bower 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation